2005
DOI: 10.1103/physrevlett.94.127202
|View full text |Cite
|
Sign up to set email alerts
|

Large Tunneling Anisotropic Magnetoresistance in (Ga,Mn)As Nanoconstrictions

Abstract: We report a large tunneling anisotropic magnetoresistance (TAMR) in (Ga,Mn)As lateral nanoconstrictions. Unlike previously reported tunneling magnetoresistance effects in nanocontacts, the TAMR does not require noncollinear magnetization on either side of the constriction. The nature of the effect is established by a direct comparison of its phenomenology with that of normal anisotropic magnetoresistance (AMR) measured in the same lateral geometry. The direct link we establish between the TAMR and AMR indicate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 13 publications
3
78
1
Order By: Relevance
“…The model also accounts for strong spin-orbit interaction present in the host valence band which splits the three p bands into a heavyhole, light-hole, and a split-off band with different dispersions. The spin-orbit coupling is not only responsible for a number of distinct magnetic [25][26][27][28] and magneto-transport [29][30][31][32] properties of ͑Ga,Mn͒As ferromagnets but the resulting complexity of the valence band was shown 14,33 to play also an important role in suppressing magnetization fluctuation effects and, therefore, stabilizing the ferromagnetic state itself. On the other hand, describing the potentially complex behavior of Mn Ga in GaAs by a single parameter may oversimplify the problem.…”
Section: Introductionmentioning
confidence: 99%
“…The model also accounts for strong spin-orbit interaction present in the host valence band which splits the three p bands into a heavyhole, light-hole, and a split-off band with different dispersions. The spin-orbit coupling is not only responsible for a number of distinct magnetic [25][26][27][28] and magneto-transport [29][30][31][32] properties of ͑Ga,Mn͒As ferromagnets but the resulting complexity of the valence band was shown 14,33 to play also an important role in suppressing magnetization fluctuation effects and, therefore, stabilizing the ferromagnetic state itself. On the other hand, describing the potentially complex behavior of Mn Ga in GaAs by a single parameter may oversimplify the problem.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The transport counterpart of MAE is anisotropic magnetoresistance ͑AMR͒, i.e., the dependence of the resistance on the angle between the magnetization and the current flow. Whereas AMR in bulk was known back in the 19th century and is a rather small effect, the recent observation of AMR in a variety of low dimensional systems, [3][4][5][6][7][8][9][10][11][12] largely exceeding bulk values, has opened a new research venue in the field of spin-polarized quantum transport. Very large AMR has been reported in planar tunnel junctions ͓tunneling anisotropic magnetoresistance ͑TAMR͔͒ with a variety of electrode and barrier materials.…”
Section: Introductionmentioning
confidence: 99%
“…Very large AMR has been reported in planar tunnel junctions ͓tunneling anisotropic magnetoresistance ͑TAMR͔͒ with a variety of electrode and barrier materials. [3][4][5][6][7][8] Enhanced AMR has also been observed in atomic sized contacts, both in the tunnel regime ͑TAMR͒ and in the contact ͑or ballistic 13 ͒ regime ͓ballistic anisotropic magnetoresistance ͑BAMR͔͒, 14 for Py, 9 Fe, 10 Ni, 11 and Co. 12 Additionally, GaMnAs islands in the Coulomb blockade regime show electrically tunable AMR. 15 Thus, a wide range of nanostructures made from different materials display enhanced AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as it has been shown in [32], the anisotropy of TMR results from the anisotropy of the current in the AFM configuration. Thus, our model does not explain the TAMR effect, which consists of a strong dependence of tunneling current on the direction magnetization in the TMR junctions in the FM configuration, as reported for some structures [10,11].…”
Section: Tunneling Magnetoresistancementioning
confidence: 87%
“…Recently, it was also reported that the magnetoresistance of the (Ga,Mn)As-based tunnel junctions is very sensitive to the direction of applied magnetic field. This so-called tunnel anisotropic magnetoresistance (TAMR) effect was observed when the saturation magnetization direction was changed in-plane [9][10][11] as well as when it was turned perpendicular to the magnetic layer [11,12]. It was also shown that the magnetization vectors of consecutive (Ga,Mn)As ferromagnetic layers separated by nonmagnetic spacers in a multilayer structure are correlated by an interlayer coupling [13][14][15][16][17] and structures exhibiting giant magnetoresistance (GMR) were obtained [14].…”
Section: Introductionmentioning
confidence: 88%